1998
DOI: 10.1037/0012-1649.34.6.1428
|View full text |Cite
|
Sign up to set email alerts
|

Infant affect and affect regulation during the still-face paradigm with mothers and fathers: The role of infant characteristics and parental sensitivity.

Abstract: This laboratory study examined mothers' and fathers' sensitivity during face-to-face interactions with their infants as well as infants' affective and regulatory responses during mother-infant versus father-infant still face (SF). The degree to which infant gender and temperament as well as parental sensitivity predicted SF responses was also examined. Participants included 94 healthy, primarily White, middle-class 4-month-olds and their parents. Results indicated that mothers and fathers were equally sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
151
4
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(175 citation statements)
references
References 31 publications
18
151
4
2
Order By: Relevance
“…These results are in accordance with previous studies (e.g., [57]) suggesting that parents are not sensitive to the same characteristics of their children. Indeed, mothers seem to be more sensitive to their children's extraversion and emotional stability, while fathers are more sensitive to their children's conscientiousness.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in accordance with previous studies (e.g., [57]) suggesting that parents are not sensitive to the same characteristics of their children. Indeed, mothers seem to be more sensitive to their children's extraversion and emotional stability, while fathers are more sensitive to their children's conscientiousness.…”
Section: Discussionsupporting
confidence: 83%
“…Rates of positive and negative responses that infants express during the still-face interaction show test-retest stability across a 2-week period (Tronick & Weinberg, 1990) and between mother and father social partners (Braungart-Rieker, Garwood, Powers, & Notaro, 1998). Studies of infant responses between 3 and 6 months are inconsistent.…”
Section: Individual Differencesmentioning
confidence: 99%
“…The findings on differences in infants' affect with mothers and fathers have been inconsistent (Braungart-Rieker, Garwood, Powers, & Notaro, 1998;Bridges & Connell, 1991;Bridges, Grolnick, & Connell, 1997;Sun & Roopnarine, 1996), and previous studies have failed either to examine differences in infant affect in relation to that of mothers and fathers or to measure infants' and parents' affect with similar observation systems. An exception is a study that found that mothers smiled more at infants during face-to-face play than did fathers and that infants smiled more at their mothers than at their fathers (Field et al, 1987).…”
mentioning
confidence: 95%
“…This might be because the still face, a dyadic task in which the parent briefly becomes unresponsive and expressionless (Tronick, Als, Adamson, Wise, & Brazelton, 1978), challenges the parent-infant relationship and the infant's emotion regulation skills. Infants typically respond to this change in interaction by displaying increased distress and attempts to regulate that distress (Braungart-Rieker et al, 1998;Cohn & Tronick, 1983;Field, Vega-Lahr, Scafidi, & Goldstein, 1986;Fogel, 1982;Murray & Trevarthen, 1985;Shapiro, Fagen, Prigot, Carroll, & Shalan, 1998;Stoller & Field, 1982;Toda & Fogel, 1993;Tronick et al, 1978;Weinberg & Tronick, 1996). The still face is accordingly considered a stressful experience for infants (Weinberg & Tronick, 1994).…”
mentioning
confidence: 99%